Involvement of prostaglandins in inflammation induced by latex of Calotropis procera. Issue 3 (2004) - Kumar Kumar, Vijay L. Vijay L.; Shivkar Shivkar, Yatin M. Yatin M.
Abstract : INTRODUCTION : The aerial parts of the plant Calotropis procera produce milky white latex that causes inflammation of the skin and mucous membranes. Prostaglandins are one of the mediators released in an inflammatory response following induction of cyclooxygenase (COX). In the present study, we have evaluated the role of prostaglandins in inflammatory response elicited by the latex of C. procera . Methods : Aqueous extract of dried latex of C. procera was injected into the 6-day air-pouch in the rat. The inflammatory response was evaluated by studying the air-pouch fluid for its volume, protein and prostaglandin (PG) E2 concentrations, and leucocyte counts. The granulation tissue from the pouch was quantified and studied for COX-2 expression by reverse transcriptase-polymerase chain reaction. The inhibitory effect of celecoxib and dexamethasone was evaluated on the aforementioned parameters. Results : Dried latex produced an inflammatory response that was maximum at 6 h. It was associated with the accumulation of protein-rich fluid, leucocytes and PGE2 production. It also resulted in granulation of the pouch cavity that was a maximum on day 3. COX-2 expression could be detected in the granulation tissue on day 1 and it increased progressively up to day 5. The anti-inflammatory drugs celecoxib and dexamethasone significantly attenuated the inflammatory response and inhibited COX-2 expression in granulation tissue. Conclusions : Latex of C. procera induces an inflammatory response characterized by an early exudative phase accompanied by PGE2 production and a late proliferative phase associated with COX-2 induction. Both the phases were effectively inhibited by COX-2 inhibitors.